Kontekst czasu w powstawaniu Konstytucji (problem wykorzystania efektu reakcji na zmianę społeczną) - Leszczyński, Leszek (Wydział Prawa i Administracji UAM, 1994)
The paper reflects on the role of time in the process of the making of a Constitution as a reaction to fundamental social transformations. The process of the making of the Polish Constitution is offered as an example. In the author's opinion, the length of time spent on the law-making is a relative value. Three groups of factors which influence the work on the Constitution have been identified. They include competence of the law-makers, unclear procedures, disputes over the contents and axiological assumptions relating to the future Constitution, political and tactic reasons. At the same time the author explains why time factor is important and how a delay beyond a certain time limit may weaken the interest in a new Constitution, or even the need for changes and new regulations to be implemented.
Time context in the making of the constitution